Two-phase flow of gas-liquid mixtures on horizontal helical pipes - Adedigba, A. G (Cranfield University, 2007)
The aim of this study was to investigate hydrodynamic two -phase (namely water and air) fluid flow characteristics in helical pipes of low amplitude and straight pipes of the same internal-diameter and constructional material: the results for the two pipes have then been compared. One of the objectives was to measure pressure, pressure drop and liquid holdup in the two pipes. These are universal dominant parameters in the oiland- gas industry as they significantly impact on the exploitation and conveyance of crude oil from wells or reservoirs to the process plant, where the crude is refined. The second objective was to examine applications of the helical pipe. Experiments were performed on three different helical pipes of internal diameters 25.4 mm, 50 mm and 100 mm and their straight counterparts. The single-phase preliminary experimental results from the 25.4 mm internaldiameter for both pipes have shown that both pressure and pressure drop are higher in the helical pipe than in the straight pipe. The friction factors were also evaluated for both pipes and found to be higher in the helical pipe than in the straight pipe. The single-phase and two-phase experimental results for the 50 mm internal-diameter pipes confirmed the conclusions from the preliminary experimental results. The two-phase results showed that slug flow occurred in the straight pipe at certain superficial velocities of air and water, whereas at the same superficial velocities of air and water, slug flow did not ensue in the helical pipe - instead bubbly flow was observed. Stratified flow occurred in the straight pipe at very low superficial velocities of air and water but under these same conditions, bubbly flow ensued in the helical pipe. A section of 100 mm internal-diameter helical pipe was installed at some distance from a catenary-shaped riser, with a view to investigating the effectiveness of the helical pipe in mitigating severe slugging. The results showed promise as the section of the helical pipe proved to be successful in reducing the menace of severe slugging. This novel finding is regarded as a breakthrough for the oil-and-gas industry in this respect. This is because hydrocarbon proven reserves in the off-shore (i.e. deep sea-water) environment have been estimated to be close to 60%. All previous research studies over the past decade to provide solution to the problem posed by severe slugging have not yielded any appreciable results. This discovery also has the advantages of reducing the demand on the topside (process) facility and the achievement of stability of liquid production is resulted from the consequent flow assurance in the pipeline and riser.